Ear-Pleasing Devices in The Police’s “Every Breath You Take” - Ariya Jati (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
This essay is concerned with sound devices in The Police’s “Every Breath You Take”. The sound devices include the rhythm, metre, and rhyme in the lyric. The study is led by the relation between poetry and music, and it is intended to allow the relation to be used in the teaching of English language and literature. The study applies a textual analysis, and it adopts Cuddon’s concept of poetic sounds. The analysis shows a rhythmical metrics in the rhyming lines of the lyric. In brief, the lyric is not musical, but it is also poetic. It is expected that the study will be suitable for general readership in English language and literature, with specific interest in music.